2012
DOI: 10.3113/fai.2012.0020
|View full text |Cite
|
Sign up to set email alerts
|

Ankle and Hindfoot Fusions: Comparison of Outcomes in Patients with and without Diabetes

Abstract: This study confirmed our hypothesis that patients with DM were at increased risk for postoperative complications after foot and/or ankle arthrodesis when compared to patients without DM. A secondary finding of this study demonstrated patients with poor short- and long-term glucose control experienced more complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
72
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 38 publications
2
72
1
1
Order By: Relevance
“…Diabetic patients experienced higher rates of infectious and noninfectious complications. Complication rates were also higher in patients with suboptimal short and long term glycemic control [32] . Ankle fractures in patients with DM are also associated with higher complication rates when compared to patients without DM [33,34] .…”
Section: Foot and Ankle Surgerymentioning
confidence: 88%
See 1 more Smart Citation
“…Diabetic patients experienced higher rates of infectious and noninfectious complications. Complication rates were also higher in patients with suboptimal short and long term glycemic control [32] . Ankle fractures in patients with DM are also associated with higher complication rates when compared to patients without DM [33,34] .…”
Section: Foot and Ankle Surgerymentioning
confidence: 88%
“…Peripheral neuropathy and a hemoglobin A1c of ≥ 8% were independently associated with SSI [31] . Arthrodesis surgery is commonly performed for foot and ankle problems in patients with DM, and complications of surgery are higher in diabetic patients [32] . A retrospective review compared 74 diabetic patients and 74 non-diabetic patients.…”
Section: Foot and Ankle Surgerymentioning
confidence: 99%
“…Costigan et al [17] reported infection in 83% of patients with diabetes lacking preoperative pedal pulses and 92% with peripheral neuropathy after surgical treatment for ankle fractures. Numerous studies have supported associations with increased wound complications and surgical site infections in patients with complicated diabetes, peripheral vascular disease, and wound compromising medications [8,16,23,36,43,44,59]. Other comorbidities associated with increased risk of postoperative infection include obesity, malnutrition, tobacco use, and immunosuppressive medication [11,21,43,45].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic patients who undergo foot and ankle surgery are particularly vulnerable to both infectious and noninfectious complications due to the comorbidities of peripheral neuropathy, Charcot neuroarthropathy, peripheral artery disease, and foot ulcers 8,9 . Increased infection rates have been observed in diabetic patients following ankle fracture repair or major foot and ankle arthrodesis 8,10,11 .…”
mentioning
confidence: 99%
“…Increased infection rates have been observed in diabetic patients following ankle fracture repair or major foot and ankle arthrodesis 8,10,11 . A retrospective controlled study demonstrated that patients with complications of diabetes had higher rates of surgical site infection after foot and ankle surgery when compared with patients with uncomplicated diabetes and patients without diabetes 6 .…”
mentioning
confidence: 99%